Uncovering hidden β-adrenergic agonist exposure from meat consumption through nationally representative human biomonitoring in Taiwan - Ho-Tang Liao; Tzu-Hsuan Peng; Chien-Jen Wang; Jing-Fang Hsu; Ching-Chun Lin; Wen-Harn Pan; Shu-Lih Chia; Pau-Chung Chen (International Journal of Hygiene and Environmental Health, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Seawater-conditioned cement as a viable substrate for coral larval settlement - Elizaldy Acebu Maboloc; Jason Hon-Yin Szeto; Ken Chue-Ho Yuen; Shirley Chun-Ching Wong; Juan Carlos Astudillo; Lin Cai; Lucen Hao; Shipeng Zhang; Apple Pui-Yi Chui; James Kar-Hei Fang (Regional Studies in Marine Science, 2025)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Coral incorporating microplastics leads to a health-risking immunometabolic shift - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li (Chemosphere, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Spatiotemporal variation in marine plankton communities driven by environmental changes in the East China sea - Chia-Ting Chen; Pei-Chi Ho; Fan-Sian Lin; Esther Wong; Fuh-Kwo Shiah; Gwo-Ching Gong; Chih-hao Hsieh (Progress in Oceanography, 2025)

A new species of Hoplostethus from Sumatra , eastern Indian Ocean , with comments on its most similar congeners ( Trachichthyiformes : Trachichthyidae ) - Yo Su; Alexander N. Kotlyar; Hsiu‐Chin Lin; Toshio Kawai; Hsuan‐Ching Ho (Journal of Fish Biology, 2025)
A new species of the roughy fish genus Hoplostethus , subgenus Leiogaster , is described based on three specimens collected from Sumatra, Indonesia. This species can be distinguished from its congeners by the following characteristics: gular region covered with ctenoid scales; pelvic‐fin spine smooth on its anterior edge; head depth subequal or smaller than its length (37.2%–38.6% standard length [SL], or 94.7%–99.2% head length [HL]); pectoral‐fin length 35.6%–37.8% SL, reaching beyond a vertical through anal‐fin origin; abdominal scutes well developed, 12–16; pectoral‐fin rays uniformly black, 17–19; gill rakers on the first arch 6–7 + 1 + 13–14 = 21; pre‐dorsal scales 24–27; and pyloric caeca 32. A detailed description is provided along with comparisons with its congeners. Additionally, diagnostic characters of the congeners and literature records of Hoplostethus rubellopterus and Hoplostethus melanopus are discussed.

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Evaluating the embryotoxicity of benzophenone-based photoinitiators in stem cells and zebrafish embryos - Chen-Yi Weng; Tzu-Ching Chang; Jun-Yang Liou; Ju-Hsin Hsu; Chia-Chi Ho; Salim Arrokhman; Pinpin Lin (Toxicology, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Correction: Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)
Bacteria with functional DNA repair systems are expected to have low mutation rates due to strong natural selection for genomic stability. However, our study of the wild-type Streptococcus pneumoniae D39, a pathogen responsible for many common diseases, revealed a high spontaneous mutation rate of 0.02 per genome per cell division in mutation-accumulation (MA) lines. This rate is orders of magnitude higher than that of other non-mutator bacteria and is characterized by a high mutation bias in the A/T direction. The high mutation rate may have resulted from a reduction in the overall efficiency of selection, conferred by the tiny effective population size in nature. In line with this, S. pneumoniae D39 also exhibited the lowest DNA mismatch-repair (MMR) efficiency among bacteria. Treatment with the antibiotic penicillin did not elevate the mutation rate, as penicillin did not induce DNA damage and S. pneumoniae lacks a stress response pathway. Our findings suggested that the MA results are applicable to within-host scenarios and provide insights into pathogen evolution.

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

Hoplostethus roseus , a new roughy fish from the western Pacific based on morphology and DNA barcoding (family Trachichthyidae) - Yo Su; Hsiu‐Chin Lin; Hsuan‐Ching Ho (Journal of Fish Biology, 2022)
A new species of the roughy fish genus Hoplostethus is described from 11 types and a non‐type specimen collected from Taiwanese waters. It can be distinguished from its congeners by a combination of characters: pectoral‐fin rays 14–17 (modally 15–16); pyloric caeca 65–84; total gill rakers 19–20; predorsal scales 18–22; oral cavity, branchial chamber, top and underside of tongue, and peritoneum uniformly black; distal margin of membrane between dorsal‐fin spines black; caudal fin without a black margin; caudal‐fin base brownish. Comparisons of the new species with similar species are provided. DNA barcoding supports the monophyly of the new species, which appears to be closely related to Hoplostethus japonicus [average cytochrome c oxidase subunit I Kimura‐2‐parameter (COI K2P) distance of 4.1%].

Evaluating the energy, health efficiency, and productivity in OECD - Ching-Cheng Lu; Yung-ho Chiu; Chih-Yu Yang; Tai-Yu Lin (Environmental Geochemistry and Health, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Integrating Patient-Specific Electrocardiogram Signals and Image-Based Computational Fluid Dynamics Method to Analyze Coronary Blood Flow in Patients during Cardiac Arrhythmias - Szu-Hsien Chou; Kuan-Yu Lin; Zhen-Ye Chen; Chun-Jung Juan; Chien-Yi Ho; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to use the computational fluid dynamics (CFD) method, patient-specific electrocardiogram (ECG) signals, and computed tomography three-dimensional image reconstruction technique to investigate the blood flow in coronary arteries during cardiac arrhythmia. Methods Two patients with premature ventricular contraction-type cardiac arrhythmia and one with atrial fibrillation-type cardiac arrhythmia were investigated. The inlet velocity of the coronary artery in simulation was applied with the measured velocity profile of the left ventricular outflow tract (LVOT) from the Doppler echocardiography. The measured patient central aortic blood pressure waveform was employed for the coronary artery outlet in simulation. The no-slip boundary condition was applied to the arterial wall. Results For the patient with irregular cardiac rhythms (Case I), the coronary blood flow rate under the shortened and lengthened cardiac rhythms were 0.66 and 0.96 mL/s, respectively. In Case II, the maximum velocity at the LVOT under a normal heartbeat was found to be 101 cm/s, whereas the average value was 73 cm/s. In Case III, the patient was also diagnosed with a congenital stenosis problem at the myocardial bridge (MCB) at the LAD. The measured blood flow rate at the MCB of the LAD for the three heartbeats in Case III was found to be 0.68, 1.08, and 1.14 mL/s. Conclusion The integration of patient-specific ECG signals and image-based CFD methods can clearly analyze hemodynamic information for patients during cardiac arrhythmia. The cardiac arrhythmia can reduce the blood flow in the coronary arteries.

Resource availability affects temporal variation of phytoplankton size structure in the Kuroshio east of Taiwan - Fan‐Sian Lin; Pei‐Chi Ho; Akash R. Sastri; Chung‐Chi Chen; Gwo‐Ching Gong; Sen Jan; Chih‐hao Hsieh (Limnology and Oceanography, 2020)
The on‐going discussion concerning how environmental factors determine phytoplankton size structure has centered around two hypotheses: (H1) The resource‐size relationship predicts that normalized biovolume size spectrum (NBSS) slopes for phytoplankton are progressively shallower with increasing resource availability and (H2) The temperature‐size relationship predicts that phytoplankton NBSS slopes steepen with increasing water temperature. To test these hypotheses, we examined 72 phytoplankton assemblage collections in the Kuroshio east of Taiwan. Total phytoplankton biomass was used as a proxy for resource availability instead of nutrients because nutrients are depleted and do not represent resource availability for oligotrophic seas. We found no significant relationship between NBSS slopes with temperature, providing little support for the temperature‐size rule. In contrast, a positive relationship between NBSS slopes and total biomass for most of the year lends general support to the resource‐size relationship, except during the winter and early spring. To explain this exception, we hypothesize that resource pulses occurring during the cold seasons are used more efficiently by small cells and promote faster growth of small relative to large phytoplankton because these pulses take place after a long period of resource depletion in oligotrophic seas; thus, the NBSS slopes become much steeper than would be expected from a positive resource‐size relationship. This deviation can be considered as nonsteady state in terms of phytoplankton size structure relative to resources. Nevertheless, we cannot rule out the possibility that grazing effects also play an important role in controlling phytoplankton size structure.

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

The impact on food security and future adaptation under climate variation: a case study of Taiwan’s agriculture and fisheries - Ching-Hsien Ho; Huu-Sheng Lur; Ming-Hwi Yao; Fang-Ching Liao; Ying-Ting Lin; Nobuyuki Yagi; Hsueh-Jung Lu (Mitigation and Adaptation Strategies for Global Change, 2018)

Development of a TaqMan probe-based insulated isothermal PCR (TiiPCR) for the detection of Acidovorax citrulli, the bacterial pathogen of watermelon fruit blotch - Pei-Yi Wu; Lien-Chun Ho; Jun-Jie Chang; Kuo-Ching Tzeng; Wen-Ling Deng; Yi-Hsien Lin (European Journal of Plant Pathology, 2017)

Effects of Porphyromonas gingivalis on Titanium Surface by Different Clinical Treatment - Nominzul Batsukh; Sheng Wei Feng; Wei Fang Lee; Sy-Jye Leu; Pei-Yo Tsai; Kuo-Ning Ho; Che Tong Lin; Ching-Hua Su; Wei-Jen Chang (Journal of Medical and Biological Engineering, 2017)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Metabolites of Scutellariae Radix Inhibit Injury of Endothelial Cells in Hypoxia Device - Chia-Lun Chao; Shiuan-Pey Lin; Yu-Chi Hou; Pei-Dawn Lee Chao; Nen-Chung Chang; Yu-Ching Huang; Feng-Ming Ho (Journal of Medical and Biological Engineering, 2015)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

Nanomedicine for glaucoma: sustained release latanoprost offers a new therapeutic option with substantial benefits over eyedrops - Tina T. Wong; Gary D. Novack; Jayaganesh V. Natarajan; Ching Lin Ho; Hla M. Htoon; Subbu S. Venkatraman (Drug Delivery and Translational Research, 2014)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Lipopolysaccharide/adenosine triphosphate-mediated signal transduction in the regulation of NLRP3 protein expression and caspase-1-mediated interleukin-1β secretion - Pei-Chun Liao; Louis Kuoping Chao; Ju-Ching Chou; Wei-Chih Dong; Chien-Nan Lin; Chai-Yi Lin; Ann Chen; Shuk-Man Ka; Chen-Lung Ho; Kuo-Feng Hua (Inflammation Research, 2013)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Application of a Sustainable Fisheries Development Indicator System (SFDIS) for Better Management Outcomes in Taiwan Offshore and Coastal Fishery - Wen-Hong Liu; Kun-Lung Lin; Hao-Tang Jhan; Ta-Ly Lin; De-Lu Ding; Ching-Hsien Ho (Coastal Management, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Trace metal cycling in the surface water of the South China Sea: Vertical fluxes, composition, and sources - Tung-Yuan Ho; Wen-Chen Chou; Ching-Ling Wei; Fei-Jan Lin; George T. F. Wong; Hui-Ling Line (Limnology and Oceanography, 2010)
We deployed floating traps in the surface waters of the South China Sea on four occasions at depths of 30 m, 100 m, and 160 m from 2006 to 2007 to quantify vertical metal fluxes in the surface water and examine trace metal composition in the sinking particles to investigate their sources. The elements determined include 13 trace metals and 8 major elements. The fluxes for most of the bioactive elements at 30 m varied markedly during different seasons and strongly co‐varied with organic matter production, but the fluxes at 160 m were low and consistent under different seasons, showing that most of the elements were internally recycled in the surface water during productive seasons. Most of the bioactive trace metals in sinking particles were correlated with biogenic P, and their P‐normalized quotas were also strongly associated with lithogenic Al. The ratios of metals to Al and P for most of the bioactive trace metals were significantly higher than the ratios in lithogenic particles and than intracellular quotas in plankton, respectively, indicating that the trace metals in the sinking particles were abiogenic, nonlithogenic, and adsorbed on biogenic particles. The comparable fluxes between aeolian deposition and the sinking particles in the mixed layer demonstrate that the highly enriched trace metals in the sinking particles were attributed to input from anthropogenic aerosols. The coupling and transport of anthropogenic trace metals with biogenic particles in oceanic surface waters may be an important mechanism for trace metal cycling in global oceans.

Cloning, expression and physiological analysis of broccoli catalase gene and Chinese cabbage ascorbate peroxidase gene under heat stress - Kuan-Hung Lin; Ho-Chang Huang; Ching-Yun Lin (Plant Cell Reports, 2010)

Regeneration of soybean (Glycine max L. Merrill) through direct somatic embryogenesis from the immature embryonic shoot tip - Murugan Loganathan; Subbiyan Maruthasalam; Ling Yin Shiu; Wei Ching Lien; Wen Hwei Hsu; Pei Fang Lee; Chih Wen Yu; Chin Ho Lin (In Vitro Cellular & Developmental Biology - Plant, 2010)

Caligus ignotus n. sp. (Copepoda: Caligidae) parasitic on Poey’s scabbardfish Evoxymetopon poeyi (Günther) off Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2010)

Development of a Methodology for Strategic Environmental Assessment: Application to the Assessment of Golf Course Installation Policy in Taiwan - Ching-Ho Chen; Ray-Shyan Wu; Wei-Lin Liu; Wen-Ray Su; Yu-Min Chang (Environmental Management, 2009)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

A revision of the family Dissonidae Kurtz, 1924 (Copepoda: Siphonostomatoida) - Geoff A. Boxshall; Ching-Long Lin; Ju-Shey Ho; Susumu Ohtsuka; B. A. Venmathi Maran; Jean-Lou Justine (Systematic Parasitology, 2008)

Two new species of taeniacanthid copepods (Poecilostomatoida) parasitic on marine fishes of Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2007)

Vertical ozone distributions observed using tethered ozonesondes in a coastal industrial city, Kaohsiung, in southern Taiwan - Ching-Ho Lin; Chin-Hsing Lai; Yee-Lin Wu; Hsin-Chih Lai; Po-Hsiung Lin (Environmental Monitoring and Assessment, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Sustainable Water Quality Management Framework and a Strategy Planning System for a River Basin - Ching-Ho Chen; Wei-Lin Liu; Horng-Guang Leu (Environmental Management, 2006)

A Method for Locating Influential Pollution Sources and Estimating Their Contributions - Ching-Ho Lin; Yee-Lin Wu; Ken-Hui Chang; Chin-Hsing Lai (Environmental Modeling & Assessment, 2004)

Naricolax insolitus n. sp., a bomolochid copepod (Poecilostomatoida) parasitic in the nasal cavities of silver pomfret Pampus argenteus off Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2003)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Species of Caligus Müller, 1785 (Copepoda: Caligidae) parasitic on marine fishes of Taiwan - Ju-shey Ho; Ching-Long Lin; Shiu-Nan Chen (Systematic Parasitology, 2000)